СИНТЕЗ ВИХРОСТРУМОВИХ ПЕРЕТВОРЮВАЧІВ З ОБ’ЄМНОЮ СТРУКТУРОЮ СИСТЕМИ ЗБУДЖЕННЯ, ЩО РЕАЛІЗУЄ ОДНОРІДНУ ЧУТЛИВІСТЬ В ЗОНІ КОНТРОЛЮ - Гальченко, В.Я.; Трембовецька, Р.В.; Тичков, В.В. (Інститут електродинаміки НАН України, Київ, 2021)
A method for nonlinear surrogate synthesis of surface eddy current probes with a volumetric structure of the excitation system was proposed. This method a priori provides a given uniform distribution of eddy current density in the testing object area where the measuring coil is located. The implementation of the task using modern metaeuristic stochastic algorithms for finding the global extremum was achieved. For the effective usage of such algorithms, taking into account the effect of velocity, metamodels of eddy current probe were preliminarily created. They were built using a productive approximation technique based on artificial radial-basis neural networks with a Gaussian activation function. Acceptable accuracy of metamodels was achieved due to the simultaneous application of the search area decomposition technologies and plural neural networks based on the techniques of associative machines with group methods for obtaining a solution. For metamodels creation a multidimensional computer experiment design with high homogeneity was used on the basis of the parameterless additive Rd-Kronecker sequence. Numerical experiments to determine the eddy current density distributions which formed by synthesized excitation structures were carried out. The advantages of using a three-dimensional structure excitation system in comparison with classical and planar ones in terms of increasing the width of the testing zone, which is characterized by uniform sensitivity, were shown. Examples of practical implementation of an excitation system with a volumetric structure for an surface eddy current probe are given. References 13, figures 8, table 1.